2012
DOI: 10.4209/aaqr.2011.09.0155
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Air Pollution and Risk of Death from Breast Cancer in Taiwan: Fine Particulate Matter (PM2.5) as a Proxy Marker

Abstract: The relationship between breast cancer mortality and air pollution was examined using an ecological design. The study areas consisted of 61 municipalities in Taiwan. Air quality data for recorded concentrations of fine particulate matter (PM 2.5 ) from study municipalities for 2006-2009 were obtained as a marker of traffic emissions and were used as a proxy for polycyclic aromatic hydrocarbons (PAHs) exposure. Age-standardized mortality rates for breast cancer mortality were calculated for the study municipali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 58 publications
(70 reference statements)
0
32
0
Order By: Relevance
“…Although most of our findings on specific cancers were not reported in the American Cancer Society study, our observations are consistent with the American Cancer Society study in a way that the excess risks of specific causes were larger than those of less specific causes (9). Our HRs per 10 mg/m 3 PM 2.5 for female genital cancer and for breast cancer were about 40% to 50% higher than the reported relative risk (1.20 and 1.19, respectively) in an ecological study of all ages in Taiwan (27,28). When compared with the American Cancer Society study, our HR per 10 mg/m 3 PM 2.5 for all-digestive organs and for male lung cancer was fairly similar to their respective HR of 1.20 and 1.43, adjusted for individual covariates and components of social factors (9).…”
Section: Discussionmentioning
confidence: 47%
“…Although most of our findings on specific cancers were not reported in the American Cancer Society study, our observations are consistent with the American Cancer Society study in a way that the excess risks of specific causes were larger than those of less specific causes (9). Our HRs per 10 mg/m 3 PM 2.5 for female genital cancer and for breast cancer were about 40% to 50% higher than the reported relative risk (1.20 and 1.19, respectively) in an ecological study of all ages in Taiwan (27,28). When compared with the American Cancer Society study, our HR per 10 mg/m 3 PM 2.5 for all-digestive organs and for male lung cancer was fairly similar to their respective HR of 1.20 and 1.43, adjusted for individual covariates and components of social factors (9).…”
Section: Discussionmentioning
confidence: 47%
“…An epidemiological association between exposure to ambient particulate matter (PM) and increased incidence of mortality and morbidity due to lung cancer and cardiovascular diseases has been demonstrated by recent studies (Pope et al, 2002;Nawrot et al, 2007;Gotschi et al, 2008;Hsieh et al, 2011;Hung et al, 2012). However, the causes of and mechanisms responsible for the adverse health effects associated with air particulate pollution are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these compounds are highly carcinogenic and/or mutagenic, several compounds have been considered as probable and possible carcinogens to humans (IARC, 1983(IARC, , 1991. Because PAHs have been frequently detected in the outdoor and indoor air of different urban area Masih et al, 2010b;Yang et al, 2010;Delgado-Saborit et al, 2011;DEFRA, 2012;Hung et al, 2012;Katsoyiannis et al, 2012;Masih et al, 2012;Alkurdi et al, 2013), they have been identified as an important class of toxic air pollutants in the atmosphere of urban areas. PAHs are present in both gas and particle phases influencing human health through inhalation and/or ingestion Ma et al, 2010;Masih et al, 2010a;Ma et al, 2011).…”
Section: Introductionmentioning
confidence: 99%